Cadangan model teoritikal bagi menilai kecekapan pelaburan dalam pembangunan Tanah Rizab Melayu - Md. Nor, Nor Ghani; Zaidi, Mohd Azlan Shah; Abdullah, Ahmad Zainuddin (Universiti Putra Malaysia Press, 1999)
The Malay Reserve (land) accounts for 33.55% of productive land in Malaysia. Unfortunately, several studies have shown that the owners of such a massive source of productive resource are not able to develop its full economic potential. The solution to this inefficient utilisation of resource requires a theory capable of explaining the source of the problem. Even though several ideas have been put forward to explain this phenomenon, few if any, are based on rigorous economic theory. This paper proposes a simple (but rigorous) theory to explain why economically rational owners of the Malay Reserve land make suboptimal investment for the development of their land. In doing so, the theory explains the underdevelopment of the Malay Reserve land. It was found that transaction cost and opportunism arising from multiple ownership and small numbers bargaining are the major factors contributing to underdevelopment of Malay Reserve land.